(untitled) (Global Journal of Medical Research, 2023)
In Japan, which is a super-aged society, people need the nursing care foods in recent years. For the prevention of aspiration pneumonia, there is a demand for safe and delicious nursing care food for not only patients but also senior citizen. To create food for swallowing that can be easily prepared even at ordinary homes, among the previous studies that have already been reported, using a type of universal design food, but that can be crushed with the tongue, for which the results have not yet been shown, is suitable or not for nursing care food is not sure. To obtain the viscosity, we investigated using eight types of thickeners and reported them. After adding 1 g, 2 g, and 3 g of each of the eight types of thickeners to commercially available shrimp gratin, a line spread test (LST) was performed using a superficial thickness measuring plate (manufactured by Saraya Co., Ltd.). As a result, by adding 1 g, it was possible to obtain a thick viscosity of 30 mm or more and less than 32 mm, which is thought to promote safe swallowing.